Oxygenated-blood colour change thresholds for perceived facial redness, health, and attractiveness. - Daniel E Re (Public Library of Science (PLoS), 2011)
Blood oxygenation level is associated with cardiovascular fitness, and raising oxygenated blood colouration in human faces increases perceived health. The current study used a two-alternative forced choice (2AFC) psychophysics design to quantify the oxygenated blood colour (redness) change threshold required to affect perception of facial colour, health and attractiveness. Detection thresholds for colour judgments were lower than those for health and attractiveness, which did not differ. The results suggest redness preferences do not reflect a sensory bias, rather preferences may be based on accurate indications of health status. Furthermore, results suggest perceived health and attractiveness may be perceptually equivalent when they are assessed based on facial redness. Appearance-based motivation for lifestyle change can be effective; thus future studies could assess the degree to which cardiovascular fitness increases face redness and could quantify changes in aerobic exercise needed to increase facial attractiveness.